Factors Associated with the Disclosure of Managers' Forecasts - William Ruland; Samuel Tung; Nashwa E. George (The Accounting Review, 1990)
[This study examines the motivation of managers to release forecasts of future earnings. Four potential motivating factors were compared for a sample of firms that reported forecasts and another sample of firms that did not release this information. The four factors are: (1) reporting good news, (2) correcting or confirming analysts' forecasts, (3) new capital offerings, and (4) ownership structure. A manager's forecast released when analysts have underestimated earnings implies good news. The relative importance of the correction or confirmation of analysts' forecasts was tested by examining the absolute errors of analysts' forecasts. Larger absolute errors of analysts' forecasts for reporting firms than for other firms imply that managers' forecasts could be correcting forecasts. Otherwise, they are confirming forecasts. The literature also suggests that some managers release forecasts prior to issuing new capital. This hypothesis was tested by examining the occurrences of new capital offerings for the reporting and comparison firms. Differences in ownership structure represent a fourth factor potentially associated with the release of forecasts. Prior literature suggests that the release of forecasts when outside holdings are relatively high can help reduce agency costs. The association of ownership structure with the release of forecasts was tested by examining the percentage of inside ownership for the reporting and comparison firms. Multivariate tests show that ownership structure, absolute errors of analysts' forecasts, and new capital offerings are significant. Absolute errors of analysts' forecasts are smaller for the forecast reporting firms than for the comparison firms, suggesting that managers' forecasts are, on average, confirmatory. The results also reveal that new capital is more likely to be issued subsequent to the date of the forecast (or equivalent date) by the reporting firms than by the comparison firms. However, the evidence is not consistent with the assumption that managers release good-news forecasts. Additional joint tests were conducted using data for the years before and after the forecast release. These tests show that absolute analysts' forecast errors and capital offerings are not significant factors for the years before or after the forecast release, suggesting that these factors reflect the motivation of managers to release earnings forecasts.]